Sifat Kimia, Fisika dan Organoleptik Selai Kulit Buah Nanas - Wahyu Mega Nanda; Reni Astuti Widyowanti; Ida Bagus Banyuro Partha (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2023)
Jam is a semi-solid food product made from a mixture of sugar and fruit. In this study, pineapple peel waste was used as the main ingredient for making jam because the use of pineapple peels is still unknown to the general public. The purpose of this study was to see the effect of adding sugar and natural citric acid on the chemical, physical and organoleptic properties of pineapple peel jam. The experimental design used the Randomized Complete Block Design (RCDB) method with 2 factors, namely the addition of sugar and the addition of natural citric acid from lime, lemon and lime with 2x repetition. The test parameters used were water content, pH, vitamin C, flavonoids, anthocyanin, and organoleptic including taste, aroma, color, and spreadability. The results showed that the addition of sugar had an effect on the test for water content, pH, vitamin C, flavonoids, and viscosity. The addition of citric acid had an effect on the water content, pH, vitamin C, flavonoids, viscosity, and anthocyanin tests. For the organoleptic test of pineapple rind jam the panelists were most interested in were the samples treated with the addition of 50% sugar and the addition of natural citric acid from lime (K3G3) with a moderately favorable score (5.01).